Safety aspects in FMS implementations - Vannas, V. (International journal of human factors in manufacturing)
The purpose of this study was to clarify what effects the organization itself has when advanced manufacturing systems are being implemented. This study was carried out at 22 Finnish flexible manufacturing system. The results showed that in the design process, companies have not paid enough attention to layout design, personnel involvement, and training.